Insects Associated with the European Mistletoe (Viscum album) in Western Ukraine: a Pilot Study - Zamoroka, A. M.; Shparyk, V. Yu.; Dovhaniuk, I. Ya.; Varga, O. O. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2023)
The first insect-targeted study of the European mistletoe, Viscum album L., was conducted in Ukraine. In total, 35 species of insects reared from mistletoe were identified to belong to 5 orders, 20 families and 34 genera. Twenty-seven identified species were reared from mistletoe for the first time, including 17 species of Hymenoptera, 8 species of Coleoptera and 2 species of Diptera. Our results revealed significant gaps in knowledge about insects associated with mistletoe. This is appeared in the fact that more than 77 % of the insects we reared have never been detected on mistletoe before. It is obviously that 70 % to 90 % of the insects associated with mistletoe remain unknown. We also found a highly probable tripartite link between the European mistletoe, parasitic fungus Sphaeropsis visci and the saproxylic and mycetophagous Coleoptera. The in[1]teraction of Coleoptera with S. visci is facultatively mutualistic, and beetles act as vectors to spread spores and mycelium among mistletoes. In addition, we found the mass breading of invasive species Leiopus femoratus on V. album. Hence, V. album might play a crucial role in the mass and rapid invasion of L. femoratus in Europe.